Mapping the concentration of nitrogen dioxide (NO2) in the air over the Nghi Son and Dung Quat refineries using Sentinel-5P Tropomi satellite data - Trinh, Le Hung; Nguyen, Duc Anh; Nguyen, Thi Thu Nga (Ecological Questions, 2025)
The petroleum industry has a significant impact on air quality during the processing of petroleum products, particularly through the emission of nitrogen dioxide (NO₂). This paper presents the results of determining the spatial distribution of NO₂ concentrations in the atmosphere over oil-refining areas by analyzing data obtained from the Sentinel-5P TROPOMI satellite instrument. The study focuses on the two largest oil refineries in Vietnam: Nghi Son Refinery (Thanh Hoa) and Dung Quat Refinery (Quang Ngai). Results show that NO₂ concentrations at the refinery locations in 2024 were consistently higher than those in surrounding regions, with peak quarterly values at Nghi Son reaching up to 77.34 µg/m³, while Dung Quat exhibited significantly lower levels, remaining below 20 µg/m³. All annual mean values were within the air-quality thresholds specified in QCVN 05:2013/BTNMT. As Sentinel-5P measures tropospheric column NO₂ rather than ground-level concentrations, these values represent relative indicators of atmospheric load. This study presents the first comparative satellite-based assessment of NO₂ pollution over Vietnam’s major oil-refining complexes, demonstrating the utility of remote sensing techniques for large-scale air quality monitoring and supporting environmental management in refinery zones.